Zinc Alginate Hydrogel-Coated Wound Dressings: Fabrication, Characterization, and Evaluation of Anti-Infective and In Vivo Performance - Adelina-Gabriela Niculescu; Alexandra Cătălina Bîrcă; George Dan Mogoşanu; Marius Rădulescu; Alina Maria Holban; Daniela Manuc; Adina Alberts; Alexandru Mihai Grumezescu; Laurenţiu Mogoantă (Gels)
The delayed healing and infection risks associated with chronic wounds and burns pose significant clinical challenges. Traditional dressings provide basic coverage but lack the bioactive properties needed for tissue regeneration and antimicrobial protection. In this study, we developed zinc alginate hydrogel-coated traditional wound dressings (WD@AlgZn) and evaluated their physicochemical properties, antimicrobial performance, and in vivo healing efficacy. Scanning electron microscopy (SEM) revealed a uniform coating of the zinc alginate network on dressing fibers, while Fourier-transform infrared spectroscopy (FT-IR) confirmed the successful incorporation of zinc ions. Antimicrobial assays further demonstrated that WD@AlgZn reduced bacterial loads (CFU/mL counts) by several orders of magnitude for both Staphylococcus aureus and Escherichia coli compared to uncoated controls. An in vivo rat burn wound model exhibited accelerated wound closure when using WD@AlgZn dressings compared to conventional wound care approaches, achieving a 90.75% healing rate by day 21, significantly outperforming the silver sulfadiazine (52.32%), uncoated-dressing (46.58%), and spontaneous-healing (37.25%) groups. Histological analysis confirmed enhanced re-epithelialization, neovascularization, and reduced inflammation in WD@AlgZn-treated tissues. The findings suggest that WD@AlgZn offers a promising alternative for advanced wound management, combining structural robustness with bioactive properties to support efficient wound healing and infection control. These results provide valuable insights into the potential clinical applications of metal-ion cross-linked biopolymeric hydrogel dressings for next-generation wound care strategies.